(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Generally, preterm newborns cannot be fed orally and human milk can be expressed (by manual expression or with the aid of a pump) and administered by gastric tube. The human milk of the mothers of these newborns has macronutrients in different concentrations, when compared to the milk of the mothers of full-term newborns. However, the effect of the different techniques of expressing breast milk on the composition of macronutrients and energy content is still unclear. Objective: To evaluate and compare the energy content of raw human milk from mothers of preterm newborns according to the way of expression. Methods: Aliquots of 0.5 ml of raw human milk extracted by electric pump and manual milking were evaluated, first determining the creamatocrit and then, through the application of mathematical formulas, the energy content. Results: 114 samples of raw human milk (colostrum and mature milk) extracted by electric pump and manual milking were evaluated. The average energy content obtained was 53.9 ± 11.6 kcal/dl in pump extraction and 58.2 ± 14.2 kcal/dl in colostrum and the average energy content in mature milk was 61.7 ± 13.2 kcal/dl in pump extraction and of 64.7 ± 13.1 kcal/dl. However, the differences are not statistically significant. Conclusion: The milking method does not seem to interfere with the energy content of human milk from mothers of preterm newborns.